Spoliation and disseisin: possession under threat and its protection before and after 1215 - Dafydd Bened Walters (Vergentis. Revista de Investigación de la Cátedra Internacional Conjunta Inocencio III, 2015)
Abstract: Each of the two great law-making events of 1215, Magna Carta and the Fourth Lateran Council, included provisions relating to dispossession (spoliation, disseisin) and how to remedy some of its previous deficiencies. This paper considers the legal texts in some detail and the history behind them, in canon law and, in relation to this topic, its Roman base; and in England, notably the legislation of the Anglo-Norman King Henry II (1154-1189). It then considers the effect of these changes in both canon and secular law after 1215 in the rest of the 13th century and a little beyond. The Anglo-Norman royal law is also compared with variants found in boroughs or cities (like London); in northern France; and in the Liber Augustalis of Frederick II for his kingdom in Sicily and southern Italy.